Current status of COVID-19 vaccination: safety and liability concern for children, pregnant and lactating women. (3rd June 2022) - Das, Swagat Kumar; Paul, Manish; Behera, Bikash Chandra; Thatoi, Hrudayanath
ABSTRACT: Introduction: Since its inception, Coronavirus disease-19 (COVID-19), caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has claimed a significant number of lives around the world. Area covered: COVID-19 vaccine development involves several vaccine platforms, including traditional live-attenuated or killed viral particles, viral vectors or DNA, and mRNA-based vaccines. The efficacy and effectiveness (EV) of these vaccines must be assessed in order to determine the extent to which they can protect us against infection. Despite the fact that some affluent countries attempted to vaccinate the majority of their inhabitants, children and pregnant women were first excluded. Expert opinion: While the severity of COVID-19 is less severe in children, the COVID-19-related complications are more severe.SARS-CoV-2 infection is also dangerous for pregnant women. The key to limiting disease spread is early discovery, isolation, and the development of safe and efficient vaccinations. As a result, the purpose of this study is to highlight the current development of various COVID-19 vaccine platforms for different groups of people at higher risk of COVID-19, with a special focus on children, pregnant and lactating women, as well as structural and pathogenicity elements of SARS CoV-2.